Knowledge and practices about multidrug-resistant tuberculosis amongst healthcare workers in Maseru - Ntambwe Malangu; Omotayo D. Adebanjo (AOSIS, 2015)
Background: To date, no study has been found that described the knowledge and practices of healthcare workers surrounding multidrug-resistant tuberculosis (MDR-TB) in Lesotho. Aim and setting: This study was conducted to fill this gap by investigating the knowledge level and practices surrounding MDR-TB amongst healthcare workers at Botsabelo Hospital in Maseru, Lesotho. Method: This was a cross-sectional survey conducted by means of a questionnaire designed specifically for this study. Data collected included sociodemographic and professional details; and responses to questions about knowledge and practices regarding MDR-TB. The questions ranged from the definition of MDR-TB to its treatment. Respondents' practices such as the use of masks, guidelines and patient education were also assessed. Results: A response rate of 84.6%(110 out of 130) was achieved. The majority of participants were women (60%), married (71.8%) and nursing staff (74.5%). Overall, less than half (47.3%) of the participants had a good level of knowledge about MDR-TB. With regard to practice, about 83%of participants stated that they used protective masks whilst attending to MDR-TB patients. About two-thirds (66.4%) reported being personally involved in educating patients about MDR-TB; whilst about 55%stated that they referred to these guidelines. Conclusion: The level of knowledge about MDR-TB amongst healthcare workers at the study site was not at an acceptable level. Unsafe practices, such as not wearing protective masks and not referring to the MDR-TB treatment guidelines, were found to be associated with an insufficient level of knowledge about MDR-TB. An educational intervention is recommended for all healthcare providers at this facility.